PHONETIC STUDIES IN AREK SUROBOYO CULTURE LANGUAGES - Nurmalita Herdiana; Yohana Kezia; Citra Dewi Kirana; Endang Sholihatin (Media Inovasi Pendidikan dan Publikasi, 2023)
The phonetic study of the language of the arek surabaya culture is an in-depth study of phonetic characteristics in the language of the surabaya community, known as